2003
DOI: 10.1038/sj.onc.1206720
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic effects of gastrin-releasing peptide in head and neck squamous cancer cells are mediated by activation of the epidermal growth factor receptor

Abstract: Head and neck squamous cell carcinomas (HNSCC) are characterized by upregulation of the epidermal growth factor receptor (EGFR), where EGFR serves as a potential therapeutic target. We previously reported that a gastrin-releasing peptide/gastrin-releasing peptide receptor (GRP/GRPR) autocrine growth pathway is activated early in HNSCC carcinogenesis. In the present study, we examined the mechanism of EGFR activation by GRP/GRPR in HNSCC proliferation. In HNSCC cells that express elevated levels of both GRPR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 50 publications
5
79
1
Order By: Relevance
“…The four receptors for the Gastrin-releasing peptide (GrP) were shown to be able to transactivate EGFR in lung, head and neck squamous tumor cells [45,46] . In addition, ligand-stimulation of GrP receptors contributed to the growth of several malignancies through the activation of diverse phospholipases and protein kinases [47] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…The four receptors for the Gastrin-releasing peptide (GrP) were shown to be able to transactivate EGFR in lung, head and neck squamous tumor cells [45,46] . In addition, ligand-stimulation of GrP receptors contributed to the growth of several malignancies through the activation of diverse phospholipases and protein kinases [47] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%
“…We previously reported that Src family kinases regulate gastrinreleasing peptide (GRP)-induced EGFR proligand cleavage leading to downstream EGFR and MAPK activation in SCCHN, which contributes to cell proliferation and invasion (15,27). In addition, blockade of endogenous GRP by using the 2A11 antibody decreased SCCHN cell proliferation and tumor growth in vivo (28).…”
mentioning
confidence: 99%
“…Our prior studies in SCCHN demonstrated that amphiregulin and TGF-ā£, but not heparin-binding-EGF or EGF, are released after treatment with GRP (27). To determine the role of TACE in GRP-mediated EGFR ligand release, we performed an amphiregulin ELISA after GRP stimulation in cell medium.…”
mentioning
confidence: 99%
“…In addition, GRP plays a role as an autocrine growth factor for cancer cells of different origins (Kim et al, 2002;Lango et al, 2002), probably mediated through activation of the epidermal growth factor receptor and MAPK (Lui et al, 2003). Inhibitors of GRP have shown promising antitumor effects in animal models (Kiaris et al, 1999;Moody et al, 2003a, b;Nock et al, 2005) and in the clinic (Chaudhry et al, 1999).…”
Section: Introductionmentioning
confidence: 99%